Surgeon’s and Caregivers’ Appraisal of Primary Cleft Lip Treatment With and Without Nasoalveolar Molding: A Prospective Multicenter Pilot Study - Broder, Hillary L. (Plast Reconstr Surg, 2016)
BACKGROUND: Despite the increasing use of nasoalveolar molding (NAM) in early cleft treatment, questions remain about its effectiveness. This study examines clinician and caregiver appraisals of primary cleft lip and nasal reconstruction with and without NAM in a non-randomized, prospective multicenter study. METHODS: Participants were 110 infants with cleft lip/palate (62 treated with NAM and 48 treated without NAM (NO-NAM)) and their caregivers seeking treatment at one of six high-volume cleft centers. Using the Extent of Difference Scale, standard photos for a randomized subset of 54 infants were rated pre-treatment and post-surgery by an expert clinician blinded to treatment group. Standard blocked and cropped photos included frontal, basal, left and right views of the infants. Using the same scale, caregivers rated their infants’ lip, nose, and facial appearance compared to the general population of infants without clefts pre-treatment and post-surgery. Multilevel modeling was used to model change in ratings of infants’ appearance pre-treatment and post-surgery. RESULTS: The expert clinician ratings indicated that NAM-treated infants had more severe clefts at pre-treatment; yet both groups were rated equally post-surgery. NAM caregivers reported better post-surgery outcomes compared to NO-NAM caregivers (p<0.05), particularly in relation to the appearance of the nose. CONCLUSIONS: Despite having a more severe cleft before treatment, infants who underwent NAM were found by clinician ratings to have comparable results to those who underwent lip repair alone. Infants who underwent NAM were perceived by caregivers to have better treatment outcomes than those that underwent lip repair without NAM.